Pengaruh Metode Demonstrasi terhadap Perilaku Sosial Anak di Kelompok B - Nurhayati, Nurhayati (Jurnal Golden Age, 2020)
The demonstration method is a very important method in showing the development of children's social behavior. The purpose of this study was to determine the effect of demonstration methods in developing social behavior of children in the Kartika XX-32 Palu Kindergarten BI Group, with a sample of 19 children enrolled in the 2019/2020 school year. The observed indicators are responsibility, courtesy, and help. The results of the study are the effect of demonstration methods on children's social behavior through the application of one-group pretest-posttest design and descriptive data analysis with calculations based on percentages. The proof is that there is a development of children's social behavior from an average of 0% before treatment to 15.78% after treatment for the category of Very Good Developing, from 10.52% to 42.1% the category of Developing as Expected, from 56.13% to 29.81% in the category of Developing, and from 33.32% to 12.27% in the category of Not Developing.